CRIMINALIZATION OF UNJUST POSSESSION IN THE LIGHT OF INTERNATIONAL DEVELOPMENTS WITH EMPHASIS ON IRAN’S CRIMINAL POLICY - Ashkan Famil Modaberan, Nader Alizadeh Seresht, Reza Nikkhah Sarnaghi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The crime of unjust possession is one of the crimes whose perpetrators somehow seek to hide the source of their criminal operations by purging it. This crime has always been considered by the legislators of the countries in the past due to its many consequences on the economies of countries and in the international community, and it has been mentioned in international documents, including the Budapest documents. This crime, because it somehow washes and cleans dirty money, has caused many of the perpetrators of this crime, who are usually white-collar workers, to easily escape the consequences and escape the clutches of justice. In the face of this phenomenon, our legislator has acted in a supra-central way and in criminalizing this crime, he has even been subjected to the private property of individuals, which is in conflict with the recognized principles of the constitution and respect for the legitimate freedoms of individuals.